BRAND ENGAGEMENT IN SELF CONCEPT PADA PEMBELIAN FASHION MUSLIM GENERASI Z DI JAWA TENGAH - Rina Sari Qurniawati; Indah Setiyo Rukmi; Yulfan Arif Nurohman (Jurnal Manajemen Dayasaing, 2023)
This research aims to examine and explain the role of Social Media Marketing and Brand Love on Brand Engagement in Self-Concept and brand loyalty. The number of samples in this study was 230 respondents who were generation Z users of Muslim fashion products in Central Java using a purposive sampling method. The analysis technique used is Path Analysis using SmartPLS version 3. The research results show that Social Media Marketing and Brand Love influence Brand engagement in self-concept and Brand Loyalty. Brand engagement in self-concept is not proven to have an effect on brand loyalty. Therefore, it is important for companies to run effective social media campaigns so that Generation Z loyalty can increase and company revenues can increase.